Award of Excellence - Zantides, Evripides (My University, 2026)
Award of Excellence for Biodapt New Logo at the 15th Worldwide Logo Design Annual-Wolda Winners, Category 1: Logos New Part 1.2: Europe & Africa.
Keywords: Humanities